Zircon (re)crystallization during short‐lived, high‐P granulite facies metamorphism (Eger Complex, NW Bohemian Massif). (20th August 2014) - Konopásek, J.; Pilátová, E.; Košler, J.; Sláma, J.
Abstract The Eger Complex in the northwestern Bohemian Massif consists mainly of amphibolite facies granitic gneisses containing a subordinate volume of felsic granulites. Microstructural changes and modelling of metamorphic conditions for both rock types suggest a short‐lived static heating from ~760 to ~850 °C at a constant pressure of ~16 kbar, which led to the partial granulitization of the granitoid rocks. Detailed study of the protolith zircon modifications and modelling of the Zr re‐distribution during the transition from amphibolite to granulite facies suggests that the development of c. 340 Ma old zircon rims in the granulite facies sample is the result of recrystallization of older (c. 475 Ma) protolith zircon. This study suggests that the partial granulitization is a result of a short exposure of the Eger Complex metagranitoids to a temperature of ~850 °C at the base of an arc/fore‐arc domain and their subsequent rapid exhumation during the Lower Carboniferous collision along the western margin of the Bohemian Massif.